2020
DOI: 10.3390/cells9061480
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prion Disease-Related Somatic Mutations in the Prion Protein Gene (PRNP) in Cancer Patients

Abstract: Prion diseases are caused by misfolded prion protein (PrPSc) and are accompanied by spongiform vacuolation of brain lesions. Approximately three centuries have passed since prion diseases were first discovered around the world; however, the exact role of certain factors affecting the causative agent of prion diseases is still debatable. In recent studies, somatic mutations were assumed to be cause of several diseases. Thus, we postulated that genetically unstable cancer tissue may cause somatic mutations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…Of note, the interplay between compositional bias and the presence of short-amyloid stretches has enabled predicting mutations impact on the aggregation propensity of prion-like proteins [65,66] in various diseases related to mammalian prion-like protein variants [67][68][69][70].…”
Section: Predicting Prion-like Proteins In Complete Proteomesmentioning
confidence: 99%
“…Of note, the interplay between compositional bias and the presence of short-amyloid stretches has enabled predicting mutations impact on the aggregation propensity of prion-like proteins [65,66] in various diseases related to mammalian prion-like protein variants [67][68][69][70].…”
Section: Predicting Prion-like Proteins In Complete Proteomesmentioning
confidence: 99%
“…In addition, differences in the local crystal structure of the TLR4-MD2-LPS complex were noted between TLR4 with the wild type allele and the G299 allele [ 20 , 21 ]. Since genetic variations confer functional alteration, these studies indicate that the rs4986790 SNP of the TLR4 gene is related to anti-bacterial functions of TLR4 [ 22 , 23 , 24 ]. Interestingly, TLR4/MD2 complex directly interacts with the Tat protein of HIV-1, and HIV-1 modulates the expression level of TLR4 and downstream immune responses, including the NF-κB pathway [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a specific analysis of PRNP gene mutations using the Cancer Genome Atlas (TCGA) database revealed a total of 48 somatic mutations in the PRNP gene in different cancers, encompassing lung adenocarcinoma, colorectal adenocarcinoma, endometrial carcinoma, head and neck squamous cell carcinoma, and melanoma [ 130 ]. Of note, five of these PRNP gene somatic mutations were considered to be pathogenic since they affect PrP C function, while four were identified as amyloid-prone PRNP somatic mutations [ 130 ]. Moreover, in pancreatic ductal adenocarcinoma cell line BxPC-3, Yang et al [ 131 ] identified six missense mutations in four major genes involved in the GPI anchor modification pathway which contributes to increased tumor cell motility.…”
Section: The Multi-faceted Role Of Prp C In Canmentioning
confidence: 99%